Impacts of Residual SNYTAX Score on The Clinical Outcomes following Percutaneous Coronary Intervention in Chronic Coronary Syndrome Patients - Wira Kimahesa Anggoro; Mohammad Saifur Rohman; Heny Martini; Pawik Supriadi; Cholid Tri Tjahjono; Yoga Waranugraha (Heart Science Journal, 2021)
Background: The residual SYNTAX score (RSS) can be used to measure the residual stenosis severity and complexity. The prognostic role of RSS in CCS patients is still unknown. We purposed to investigate the impact of RSS on the clinical outcomes following PCI in CCS patients. Methods: A prospective cohort study was performed. Based on the residual SYNTAX score, patients were divided into three groups: RSS 0, RSS 0 to 9.5, and RSS >9.5. The primary outcome was patient-oriented composite endpoint (POCE), including repeat revascularization, myocardial infarction, and all-cause mortality. Results: After 1-year follow-up period, patients in RSS >9.5 group revealed the greater POCE (4.3% vs. 6.4% vs. 23.9%; p = 0.016) than others. The repeat revascularization rate also was greater in the RSS >9.5 group (0.0% vs. 6.4% vs. 19.6%; p = 0.012). However, the hospitalization due to angina rates in all groups was not significantly different (4.3% vs. 4.2% vs. 4.3%; p = 1.000). The multivariate analysis revealed that RSS >9.5 was the strong predictor for repeat revascularization during 1 year follow-up (Odds ratio [OR] = 9.605; 95% confidence interval [CI] = 1.207 - 76.458; p = 0.033). Conclusion: The greater RSS was associated with the higher 1-year POCE and repeat revascularization rate in CCS patients. The high RSS was also the strong predictor for 1-year repeat revascularization for CCS patients.